2018
DOI: 10.1007/s00360-018-1146-5
|View full text |Cite
|
Sign up to set email alerts
|

Immune challenges decrease biliverdin concentration in the spleen of northern Bobwhite quail, Colinus virginianus

Abstract: Most antioxidants have multiple functions; in addition to minimizing oxidative damage, many antioxidants have immune-modulating properties. For example, biliverdin is produced in the liver and spleen from the breakdown of heme, and has putative immune-suppressing and antioxidant properties. However, the majority of these properties have been investigated in vitro or in mammalian models, in which biliverdin reductase converts virtually all biliverdin to bilirubin. Thus, biliverdin's physiological roles remain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…As an intermediate metabolite in heme metabolism, biliverdin has long been regarded as a mere waste product excreted in bile. However, recent studies have revealed that it has many therapeutic effects on the human body, including antioxidant and anti-inflammatory properties (Vasavda et al 2019 ; Shiels et al 2020 ; McDonagh 2010 ; Gonzalez-Sanchez et al 2016 ), suppression of the immune response (Baylor and Butler 2019 ; Homsher et al 2018 ), stabilization of vascular endothelial cells (Nakao et al 2005 ; Li et al 2021 ), and regulation of cell apoptosis (Zheng et al 2014 ; Moraes et al 2012 ). Biliverdin is expected to be a potential therapeutic drug for many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…As an intermediate metabolite in heme metabolism, biliverdin has long been regarded as a mere waste product excreted in bile. However, recent studies have revealed that it has many therapeutic effects on the human body, including antioxidant and anti-inflammatory properties (Vasavda et al 2019 ; Shiels et al 2020 ; McDonagh 2010 ; Gonzalez-Sanchez et al 2016 ), suppression of the immune response (Baylor and Butler 2019 ; Homsher et al 2018 ), stabilization of vascular endothelial cells (Nakao et al 2005 ; Li et al 2021 ), and regulation of cell apoptosis (Zheng et al 2014 ; Moraes et al 2012 ). Biliverdin is expected to be a potential therapeutic drug for many diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The source of biliverdin deposited in the eggshell by female birds is thought to be in the uterus (Hargitai et al 2017). However, the exact connection between the biliverdin destined to colour the eggshell and that derived from the systemic degradation of the erythrocytes has yet to be described (Homsher et al 2018). Several studies on different species have found a link between eggshell colouration and female body condition, some of which provide support for a condition‐dependence of biliverdin‐based egg colour by following an observational approach (Moreno et al 2005, 2013, Siefferman et al 2006, Hanley et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if immune challenges affect circulating triglyceride levels, then biliverdin concentration may also change proportionally via an unidentified mechanism. Given the nascent stage of research into the physiological roles of biliverdin in non-mammalian systems (Homsher et al, 2018;Butler and Ligon, 2015), documenting such potential associations may allow for development and refinement of more specific hypotheses.…”
Section: Introductionmentioning
confidence: 99%